Prevalence and distribution of pathogenic genes in Campylobacter jejuni isolated from poultry and human sources - Leonardo Moreira Lima; Gustavo Perdoncini; Karen Apellanis Borges; Thales Quedi Furian; Carlos Tadeu Pippi Salle; Hamilton Luiz de Souza Moraes; Vladimir Pinheiro do Nascimento (Journal of Infection in Developing Countries)
Introduction: Campylobacter jejuni is one of the most common bacterial causes of human gastroenteritis. Despite its public health importance, the virulence factors and mechanisms underlying C. jejuni pathogenesis remain poorly understood and the relationships between these genes and the sources of the strains are not clear. We aimed to determine the virulence profiles of C. jejuni isolated from poultry and human cases of Campylobacteriosis.